Sustaining the Islamic marriage institution in Malaysia: lessons from qur’anic stories - Mohmad, Nor Zatu Amni; Abdul Malek, Normi; Samsudin, Sofiah; Jani, Nazrul Affandi (International Institute of Islamic Thought and Civilization (ISTAC), 2019)
Divorce rates are rising in Malaysia and as a consequence, the sacred Islamic marriage institution is directly affected by this phenomenon. It was reported that the number of divorces in 2010 was 28,035 and it increased rapidly to 48,077 as of July 2016. JAKIM has identified ten major causes of divorce in Malaysia which are: irresponsibility, weak Islamic foundation, third party interference, cultural differences, sexual issues, financial crisis, career dilemma, health problems, moral decay and communication obstacles. Al-Qur'an contains several narratives on marital relationship, which can serve as examples for married couples. This study critically investigates to what extent these Qur’ānic references may guide a married couple’s better understanding of their roles and duties as husband and wife, thus significantly enhancing their quality of marriage. The research proves that marital life is an arena for jihad, which means married couples must strive and make their utmost effort to strengthen their marriage. Virtues such as humility, patience and honesty are prime qualities in a marriage, whereas vices such as irresponsibility, arrogance and infidelity are detriments. The research highlights solutions for almost every cause of divorce as identified by JAKIM, which expects to reduce the divorce rate and sustain the Islamic marriage institution in Malaysia. Finally, it is recommended that JAKIM should consider including the research findings in its post-marital course as it is one of the best platforms to propagate the Qur’ānic stories of husbands and wives to Muslim married couples in Malaysia.